2022
DOI: 10.3389/fpsyg.2022.925727
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization (bullying) on mental health, behavioral problems, cognition, and academic performance in preadolescent children in the ABCD Study

Abstract: ObjectivePeer victimization is a substantial early life stressor linked to psychiatric symptoms and poor academic performance. However, the sex-specific cognitive or behavioral outcomes of bullying have not been well-described in preadolescent children.MethodsUsing the baseline dataset of the Adolescent Brain Cognitive Development (ABCD) Study 2.0.1 data repository (N = 11,875), we evaluated associations between parent-reported bullying victimization, suicidality (suicidal ideation, intent, and/or behavior), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
(106 reference statements)
2
5
1
Order By: Relevance
“…The association between general victimization and lower executive function was not found in our study, which is inconsistent with a recent study also conducted using ABCD data [ 20 ]. This might due to the differences in the way bullying was measured, as parent-reported dichotomous victimization (yes or no) variable based on KSADS was used in Menken et al’s study, whereas continuous victimization and perpetration variables measured by total score of 18 items in the self-reported PEQ questionnaire were used in our study, and we included both victimization and perpetration in the GLMM model in order to obtain a clearer picture of the relationship between peer bullying and children’s developmental outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The association between general victimization and lower executive function was not found in our study, which is inconsistent with a recent study also conducted using ABCD data [ 20 ]. This might due to the differences in the way bullying was measured, as parent-reported dichotomous victimization (yes or no) variable based on KSADS was used in Menken et al’s study, whereas continuous victimization and perpetration variables measured by total score of 18 items in the self-reported PEQ questionnaire were used in our study, and we included both victimization and perpetration in the GLMM model in order to obtain a clearer picture of the relationship between peer bullying and children’s developmental outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, ample research evidence has underscored both bullying victimization and peer perpetration as established risk factors for suicide ideation (SI), suicide attempt (SA), and non-suicidal self-injury (NSSI) [ 14 20 ], while these associations might be different across subtypes of peer bullying. For instance, previous studies have confirmed the predictive effect of direct victimization (i.e., overt) rather than indirect victimization (i.e., relational, reputational) on SI [ 9 , 21 23 ], while inconsistent results exist [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies, we found that bullied children had poorer reading ( Mundy et al, 2017 , Menken et al, 2022 ) and inhibitory control ( Samper-García et al, 2021 , Poon, 2016 , Menken et al, 2022 ) than non-bullied children. Lacking emotional regulation may worsen the effects of bullying because of its role in adapting to stressful or traumatic events ( Frederick and Le Menestrel, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…The temporal precedence of the variables used was as follows. We calculated the effect of being bullied on cognition, because while several studies have implicated an association between victimization and lower cognitive scores ( Menken et al, 2022 , Poon, 2016 , Samper-García et al, 2021 ), cognition did not influence the likelihood of being bullied ( Miguel and Urzúa, 2015 ). Additionally, a study of social defeat stress in mice showed rodents that were victimized had dendritic atrophy ( Fox et al, 2020 ), which can impact regional brain volume.…”
Section: Methodsmentioning
confidence: 99%